1980
DOI: 10.1084/jem.151.6.1468
|View full text |Cite
|
Sign up to set email alerts
|

Immune response genes control T killer cell response against Moloney tumor antigen cytolysis regulating reactions against the best available H-2 + viral antigen association.

Abstract: Cytolytic T lymphocytes (CTL) specific for the virus-induced and leukemia-associated Friend, Moloney, Rauscher (FMR) antigen are easily detected in the spleens of primary and secondary stimulated H-2b or H-2d mice. They react, respectively, with H-2Db + FMR and H-2Kd + FMR; Dd and Kb never being involved. On the other hand, recombinant (KbDd) mice are relatively low responders that produce CTL only after secondary stimulation. Competition and blocking experiments with monospecific anti-H-2 antibodies have demo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
12
0

Year Published

1981
1981
1990
1990

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(12 citation statements)
references
References 20 publications
0
12
0
Order By: Relevance
“…Many H-2-1inked regulatory mechanisms have been proposed. It has been demonstrated that loci within the H-2 complex control the levels of virus replication (as demonstrated in vitro for cultured tumor cell lines by Wolfe and Blank 1986) the immune responses to viral antigens such as the level of anti-viral antibodies, the delayed-type hypersensitivity response, and the generation of specific cytolytic T lymphocytes (Britt and Chesebro 1983, Colombatti et al 1979, Gisselbrecht et al 1978, Gomard et al 1980, Green 1984, Lilly et al 1975, Lonai et al 1981, Meier et al 1973, Meruelo 1979, Nowinski 1976, Nowinski et al 1979, Tucker et al 1977, Vasmel et al 1988, Vlug et al 1981. Development of the immunodeficiency induced by LP-BM5 MuLV could be dependent on one of these H-2-1inked regulatory mechanisms.…”
Section: Discussionmentioning
confidence: 96%
“…Many H-2-1inked regulatory mechanisms have been proposed. It has been demonstrated that loci within the H-2 complex control the levels of virus replication (as demonstrated in vitro for cultured tumor cell lines by Wolfe and Blank 1986) the immune responses to viral antigens such as the level of anti-viral antibodies, the delayed-type hypersensitivity response, and the generation of specific cytolytic T lymphocytes (Britt and Chesebro 1983, Colombatti et al 1979, Gisselbrecht et al 1978, Gomard et al 1980, Green 1984, Lilly et al 1975, Lonai et al 1981, Meier et al 1973, Meruelo 1979, Nowinski 1976, Nowinski et al 1979, Tucker et al 1977, Vasmel et al 1988, Vlug et al 1981. Development of the immunodeficiency induced by LP-BM5 MuLV could be dependent on one of these H-2-1inked regulatory mechanisms.…”
Section: Discussionmentioning
confidence: 96%
“…CTL specificity for target antigens was analyzed by two approaches: (a) addition of varying numbers of competitor target cells to the SXCr release cytotoxicity assay (5) and (b) addition of anti-H-2 sera at varying dilutions, in the absence of complement, to the 51Cr release cytotoxicity assay (1,11). The percentage of inhibition of CTL-mediated cytotoxicity by both approaches was calculated according to the formula: control -experiment/control × 100, where control was the specific cytotoxic activity detected in positive control wells; and experiment was the experimental cytotoxicity values obtained from wells containing competitor target cells or blocking antisera.…”
Section: Methodsmentioning
confidence: 99%
“…Thus, joint recognition of H-2 and tumor antigens by syngeneic C T L has been reported for tumors induced by murine leukemia viruses (MuLV; 1-6), by Simian virus-40 (SV40) (7,8), and by Herpes simplex virus (9), as well as for chemically induced tumors whose antigenic structure has not yet been clearly defined (10). The general consensus is that the M H C antigens involved in the recognition of the tumor target cell by the C T L are restricted to the antigens coded by two genes, H-2K and H-2D; the antigens coded by genes in the H-2I region and in other regions of H-2 do not appear to be required for the recognition event (5,(11)(12)(13). Finally, the involvement of H-2K and Ho2D has been shown not to be equivalent in all cases, such that tumor antigen recognition by C T L was preferential for an association of tumor antigen with H-2K or H-2D antigen (2,5,(11)(12)(13), depending on the origin of the tumor and on the H-2 haplotype of the CTL.…”
mentioning
confidence: 99%
See 2 more Smart Citations